A radionuclide study of regional gastric motility - Ham, H R; Muls, V; Cadiere, G B; Froideville, J L; Urbain, D (Nuclear medicine communications, 1995)
The aims of this research were to study some methodological aspects of radionuclide methods for assessing regional gastric motility and to determine the parameters that can be extracted along with their normal values or patterns. During the lag phase, the antral contraction curve showed three different patterns. At the beginning, the antral activity was too low to be analysed. Irregular variation of the count rate was then observed, followed by a more regular contraction. The application of Fourier transformation to the well-defined cyclical count rate variations revealed two areas with high amplitude values but with phase opposition. No peristaltic wave could be identified. After the lag phase, the antral curve showed cyclical variations of count rates with a frequency of about three cycles per minute. Slightly displaced curves but with a much lower amplitude were observed at different parts of the stomach. Several factors were found to influence the antral contraction curve, including the choice of region of interest and time since the last meal. Irregularities in the antral curve, both in terms of frequency and of amplitude, were not unusual in healthy subjects. These should be taken into account when interpreting antral contraction curves. The phase image showed a well-defined peristaltic contraction pattern. Three 360 degrees cycles were usually observed throughout the stomach, suggesting that the time necessary for a peristaltic wave to sweep through from the upper part of the stomach to the antrum is about 1 min. Similar phase images were obtained in all subjects regardless of the amount of time since the meal containing the radioactive tracer, suggesting that gastric peristalsis can easily be assessed and interpreted. The amplitude image showed high amplitude in the antral area and in the greater curvature of the stomach. In the lesser curvature, the amplitude was much lower. Unlike the phase image, however, there was marked variability in the regional amplitude distribution. The value of the regional amplitude distribution for evaluating regional gastric motility is therefore limited.